Impedance spectroscopy of p-ZnGa2Te4/n-Si nano-HJD - Fouad, S. S.; Sakr, G. B.; Yahia, I. S.; Abdel-Basset, D. M.; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
The dielectric relaxation and alternating current mechanisms of nano-crystalline p-ZnGa2Te4/n-Si heterojunction diode (HJD) were investigated by complex impedance spectroscopy over a wide range of temperature (297-473 K) and a frequency range (42 Hz-5 MHz). The bulk resistance R-b as well as the bulk capacitance C-b were found to increase with increasing temperature. The dc conductivity exhibits a typical Arrhenius behavior. The electrical activation energy Delta E-sigma was determined to be (0.28 eV). The ac conductivity spectrum was found to obey Jonscher's universal power law. The frequency exponent s decreases slightly with increasing temperature. The temperature dependence of ac conductivity can be reasonably interpreted in terms of the correlated barrier hopping (CBH) model. The dielectric constant epsilon(1)(omega) and dielectric loss epsilon(2)(omega) were found to decrease with increasing frequency and to increase with increasing temperature. The mean value of the exponent m decreases with increasing temperature. The dielectric analysis is described by non-Debye type behavior. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: ZnGa2Te4 defect chalcopyrite; Nano-heterojunction diode; Impedance spectroscopy; CBH model; Electric modulus; Dielectric properties